2016
DOI: 10.1017/s0376892916000291
|View full text |Cite
|
Sign up to set email alerts
|

Chronic anthropogenic disturbance as a secondary driver of ant community structure: interactions with soil type in Brazilian Caatinga

Abstract: SUMMARYHabitat loss is widely recognized as the major cause of global biodiversity decline, but remaining habitat is increasingly threatened by chronic human disturbances. Using a multi-model averaging approach we examined the association between five chronic disturbance surrogates and the richness and taxonomic and functional composition of ants in Brazilian Caatinga. Using pitfall traps in 47 plots near Parnamirim city (Pernambuco) across two soil types (sand and clay), we recorded 53 species from 27 genera.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
(76 reference statements)
3
17
0
Order By: Relevance
“…Such results are contrary to those of Leal, Andersen, & Leal, (), who found at another Caatinga location that CAD had negative effects on the abundance of high‐quality dispersers and consequently on seed dispersal services by ants. However, our study was conducted on sandy soils while the previous study included clay soils, and Caatinga ant communities on sandy soils have been previously shown to be particularly resilient to CAD (Oliveira, Ribeiro‐Neto, Andersen, & Leal, ). In addition, mean annual rainfall in the previous study was only 550 mm, at the arid extreme of our study, and this might also be a factor explaining the higher sensitivity of seed‐disperser ants to disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Such results are contrary to those of Leal, Andersen, & Leal, (), who found at another Caatinga location that CAD had negative effects on the abundance of high‐quality dispersers and consequently on seed dispersal services by ants. However, our study was conducted on sandy soils while the previous study included clay soils, and Caatinga ant communities on sandy soils have been previously shown to be particularly resilient to CAD (Oliveira, Ribeiro‐Neto, Andersen, & Leal, ). In addition, mean annual rainfall in the previous study was only 550 mm, at the arid extreme of our study, and this might also be a factor explaining the higher sensitivity of seed‐disperser ants to disturbance.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that CADs and rainfall influence plant (Ribeiro et al., ; Ribeiro et al. ; Rito et al., ) and ant (Oliveira et al., ; Ribeiro‐Neto et al., ) community structure and composition in the Caatinga. We also observed that CADs and rainfall levels were associated with changes in the compositions of EFN‐bearing plant communities and attendant ant communities, supporting part of our third hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although such networks occur in many different ecosystems (Rico‐Gray & Oliveira, ), the protection provided by ants to EFN‐bearing plants appears to be particularly effective in arid environments (Leal & Peixoto, ). However, arid environments usually experience significant anthropogenic disturbance (Miles et al., ), which can lead to declines in the abundance of specialist EFN‐bearing plants (Leal et al., ), the abundance of specialist arboreal ants (Oliveira et al., ) and ant visitation rates (Leal et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations